Investigating The Determinant of Indonesian Citizens' “Mudik” Intention Post Covid-19 Pandemic - Fatchur Rohman (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2023)
The pandemic outbreak of Covid-19 made individuals and society adjusted their social activities and behavior, following the social distancing regulations to slow the spread of the virus. Over 2 years, the regulation has been followed by vaccination programs that could help citizens build better immunity against the virus. In Indonesia, the social distancing regulations restricted several activities and customs by the citizens, one of which is the “Mudik” customs. Following the social distancing regulations that have been slowly adjusted by the improvement of the individual immune system toward the virus, some of the restrictions have been lifted by the Indonesian Government which includes the adjustment of the Mudik restrictions. This opens opportunities to identify the factors that could affect Indonesian Citizens' intention to return to their old Mudik customs post the Covid-19 Pandemic. The current research follows the suggestion that perceived knowledge could become an important construct in determining individual future behavior. To prove the suggestion, we adopt the Theory of Planned (TPB) model to examine the relationship of perceived knowledge toward individual future intention, in the case of Mudik behavior by the Indonesian Citizen post the Covid-19 pandemic. 238 Indonesian citizens participated in the current research as research respondents, and we used the Partial Least Square (PLS) analysis to examine the suitability of our proposed conceptual framework to explain the relationship between perceived Covid-19 knowledge toward the main construct of the TPB Model. The research findings showed that perceived Covid-19 knowledge is one of the factors that could determine Indonesian Citizens' Mudik behavior. A comprehensive discussion of current research results and their theoretical and practical implication are presented within the article.